Technopreneurial STEM Teaching: Integrating Business, Curriculum, and Education - Jaka Wijaya Kusuma; Hamidah Hamidah; Syamsul Hidayat; Diana Permata Nazibah; Melinda Rochmah; Suci Tiara Saurma; Ratna Suminar (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to explain how technopreneurship learning tools in school education and STEM integration implemented Technology in the business world. The method used in this study is the System Literature Review method by adding Field Studies at Al-Mubarok High School. Technopreneurship learning tools in this study are needed in learning both in the classroom and the field. The stages of developing technopreneurship learning tools are obtained through integrated systematic STEM, which is carried out through stimulating students' interest in doing business and entrepreneurship, building trust in Self, developing creativity and innovation, and daring to take risks. In this curriculum, the involvement of educators with experience in entrepreneurship dramatically determines how the process encourages students' interest to be involved in entrepreneurship and the business world, especially in the learning process in the world of Education